2018
DOI: 10.1242/jeb.186700
|View full text |Cite
|
Sign up to set email alerts
|

Jumping mechanics of desert kangaroo rats

Abstract: Kangaroo rats are small bipedal desert rodents that use erratic vertical jumps to escape predator strikes. In this study we examined how individual hind limb joints of desert kangaroo rats (Dipodomys deserti) power vertical jumps across a range of heights. We hypothesized that increases in net work would be equally divided across hind limb joints with increases in jump height. To test this hypothesis, we used an inverse dynamics analysis to quantify the mechanical output from the hind limb joints of kangaroo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…(2006); Picker et al. (2012); Schwaner et al. (2018); Sutton and Burrows (2011); and Mendoza (2018).…”
Section: Methodsmentioning
confidence: 99%
“…(2006); Picker et al. (2012); Schwaner et al. (2018); Sutton and Burrows (2011); and Mendoza (2018).…”
Section: Methodsmentioning
confidence: 99%
“…The phrase that describes a quantity equal to the increase in muscle force, ground reaction force or joint moment divided by the time interval of that increase. In our previous study, kangaroo rats jumped over a vertical barrier from a standing posture (Schwaner et al, 2018). The GRF vector (red arrow) was measured using a force plate.…”
Section: Rate Of Force Developmentmentioning
confidence: 99%
“…More specifically, in movements that involve leaving the ground, such as jumping or leaping, takeoff velocity needs to be maximized to achieve the greatest distance (Garcia-Ramos et al, 2015). We have been studying vertical jumping mechanics in kangaroo rats, which are capable of vertically jumping to 10 times their standing hip height (Biewener and Blickhan, 1988;Schwaner et al, 2018) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high power outputs calculated in the study, these authors found support for the use of elastic energy during jumping. Studies of bipedal rodents [lesser Egyptian jerboas (Moore et al, 2017b), banner-tailed kangaroo rats (Biewener & Blickhan, 1988) and desert kangaroo rats (Schwaner et al, 2018)], however, have not found evidence for power amplification via elastic energy storage; these species rely solely on power production by their enlarged hindlimb muscles during jumps. Because of this, bipedal rodents are capable of faster jumps with higher force production and accelerations.…”
Section: Discussionmentioning
confidence: 99%